Specialized vocabulary across languages: The case of traditional Chinese medicine - Lu, Cailing; Coxhead, Averil (Studies in Second Language Learning and Teaching, 2023)
This paper reports on the creation of specialized word lists in traditional Chinese medicine (TCM), which is a discipline using vocabulary across languages (i.e., Chinese and English) and involves learners with different L1 backgrounds. First, a TCM Word List of 2,778 specialized words was established from corpora of TCM textbooks and journal articles. Selection criteria included specialized meaning, keyness in a corpus of general written English compared to the TCM Corpora, and frequency. The resulting TCM list covered 36.65% of the TCM Corpora but had low coverage over corpora of general written English and medical English. The TCM Word List was then divided into three sub-lists based on frequency, and graded into three levels. Level 1 contains high-frequency lexical items in English (e.g., organ, coating); Level 2 contains items that are mid-, low-frequency, or beyond any frequency levels (e.g., pericarpium, metabolism); and Level 3 contains Chinese loan words (e.g., qi, yang). Last, there is an overlap of 309 word families between this list and an earlier TCM list by Hsu (2018), which excludes words from the 1st-3rd 1,000 word families in English. Suggestions for teachers and future research are provided.